Analisis Pemecahan Beban Penyulang Kalipare 20 kV - Sri Wahyuni Dali; Imron Ridzki; Muhammad Fahmi Hakim; Hana Nabilla Hapsari; Latasha Fadiela Nurlakshita (Elposys: Jurnal Sistem Kelistrikan, 2022)
The Kalipare feeder is a feeder located at PT PLN (Persero) ULP Sumberpucung where the feeder has a feeder length of 232.9 kms and a load of 161.8 A, with a voltage drop of 17.981 kV, the energy loss that is not channeled in 40.82 minutes is IDR 5,333,734.00. So with that the feeder is carried out there is a splitting of the load into two, namely 86.6 A and 74.4 A, with the end voltage being 19.27 kV, with the energy loss that is not channeled in 40.82 minutes is Rp. 2,454.510.8. This load solving is carried out based on the existing conditions of the Kalipare Feeder in 2019, as well as modeling in the form of simulations using ETAP 12.6 and analyzing the simulation results with the existing load breaking conditions in 2020. Load splitting locations are carried out at 7 points taking into account the value of the investment to be made used to do the job. The locations where the load splitting will be carried out are GI Karangkates, Perempatan Peteng, Tumpakmiri, Kalipare, and Banduarjo with an investment cost of Rp. 21,124,247,696 with the construction of 527 gates. After breaking the load, which resulted in the Kalipare feeder and the Donomulyo feeder, the value of the voltage drop on the Kalipare feeder decreased to 18.25 kV; 8.70%, while the Donomulyo Feeder is 19.241 kV; 3.84%. The solution to the load of the Kalipare feeder will minimize losses due to blackouts and increase customer satisfaction.